Spectrum of Upper GI Endoscopy in Children: A Tertiary Centre Experience from Bangladesh - Mahmud, Salahuddin; Gulshan, Jahida; Baidya, Madhabi; Rashid, Rafia; Tasneem, Farhana; Hasan, Ahmed Rashidul; Farhana, Tanzila; Begum, Dilruba; Asha, Nafis Fatema; Ahmed, Syed Shafi (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Upper gastrointestinal endoscopy is an essential, safe and sensitive investigation for diagnosing pediatric gastrointestinal diseases. In resource-limited countries like Bangladesh, the practice of pediatric endoscopy remains rudimentary, lacking in trained pediatric endoscopists and appropriate-sized endoscopes. There is limited study on paediatric upper GI endoscopy in our country. Objectives: The aim of the study was to find out the indications, common endoscopic findings and immediate post procedure complication of UGI endoscopy in children. Methods: This is a retrospective study; the records of all the patients whose age is less than 18 years and who underwent endoscopy in the last 6 years were studied. Results: Among the total of 384 children (age <18 years), the most common indications were recurrent abdominal pain in 133 (34.7%) patients followed by hematemesis±melena in 99 (25.8%), esophageal varices (follow up with eradication) in 67 (17.5%), recurrent vomiting in 31 (8.1%), foreign body, CLD screening, suspected celiac disease, isolated splenomegaly, corrosive injury, and weight loss. The most common abnormal findings were gastritis in 103 (26.9%) children followed by esophageal varices in 73 (19.2%), duodenitis in 26 (6.8%), foreign body, esophagitis, hiatus hernia, esophageal stricture, esophageal ulcer, gastric ulcer, duodenal ulcer etc. Minor adverse events occurred in 7.0% of children. Conclusion: The commonest indication for Pediatric UGI endoscopy was recurrent abdominal pain and the commonest endoscopic feature was gastritis. No significant post procedure complication was noted in the study. DS (Child) H J 2021; 37(2): 123-128